United : thoughts on finding common ground and advancing the common good - Booker, Cory (Ballantine Books, 2016)
An energetic new voice in American politics, United States Senator Cory Booker sounds a stirring call to reorient our civic discourse around the principles of empathy and solidarity. Telling candid, inspiring stories from his life and career, and imparting lessons learned from people who motivated him to serve, he speaks of rising above discord, tending to our shared resources, and embracing our common destiny. --Publisher